Polyacrylonitrile/Polyurethane Nanofiber/Boron Nitride Nanosheet Sponges for Noise Reduction; ACS Applied Nano Materials; Vol. 8, iss. 22 - Jiaxin Zhao; Sai Wang; Zixin Dai; Surmenev R. A. Roman Anatolievich; Shichao Zhang; Jianyong Yu; Bin Ding (2025, 2025)
Title screen